(untitled) (Discourse of Law and Administration, 2021)
The article analyzes the key issues related to the combination of restriction of liberty with imprisonment. It discusses substantive law issues, including the principle of combining sentences of different types, as well as procedural issues, related to the modes of combining sentences and the applicable procedure, in particular in proceedings for issuing a joint sentence. The analysis was carried out on the basis of the currently binding provisions of the Polish Criminal Code and the Code of Criminal Procedure, in the wording established, among others, by the so-called anti-covidencelaws. The author discusses issues connected with the method of proceeding on the subject of merging sentences, which raise interpretation doubts in practice, and formulates de lege lata postulates in thisregard. Assessing the current rules